Membangun Jiwa Yang Sehat Menurut Ajaran Islam - Zaitun Zahra; Eko Nursalim (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
Mental health problems are increasingly widespread and a serious issue that needs to be addressed, with around 450 million people worldwide, including in Indonesia, experiencing mental disorders. Suicide cases in Indonesia show an alarming trend. According to the data obtained, suicide is one of the leading causes of death among adolescents and adults. Therefore, it is important to have treatment or provision as early as possible to avoid this. In this context, Islam as a comprehensive religion has provided guidance for each individual to maintain mental health, such as through the practice of worship and so on. This research aims to examine how to build a healthy soul according to Islamic teachings that can be applied in everyday life. The method used is qualitative research with a library research approach, namely by examining texts or documents that are in accordance with the issues raised. The results showed that Islam teaches several important principles for maintaining mental health, including tawakkal (surrender to Allah), patience, gratitude, dhikr, maintaining a balance between the life of the world and the hereafter, community and social support, and the importance of education and knowledge. These principles can be the basis for efforts to prevent and treat mental health problems, in addition to practising these principles will increase one's faith.